Cyber operations in Russia's war against Ukraine: Uses, limitations, and lessons learned so far - Matthias Schulze; Mika Kerttunen (Stiftung Wissenschaft und Politik (SWP), 2023)
One year after Russia's invasion of Ukraine, certain assumptions about the utility of cyber operations during wartime can now be put to the test. Russian cyber salvos opened this war, but they failed to achieve their objectives in the face of a resilient cyber defender. Joint cyber/conventional warfighting is still hard to implement due to its uncertain effects, the potential for spill-over, malware development cycles, and differing operational tempos. Cyber operations against Ukraine have not (yet) achieved major strategic effects in reducing Ukraine's capacity to resist. Additionally, Russian information operations targeting Ukrainian and Western audiences fell on deaf ears. The greatest value of cyber operations therefore still appears to lie in their intelligence and reconnaissance functions.
Keywords: 320; cyber operation; cyber attack; cyber forces; cyber capabilities; counter-force capability; cyber warfare; Russia-Ukraine war; Cyber Pearl Harbour; Operation Glowing Symphony; Advanced Persistent Threat; APT; Computer Emergency Response Team of Ukraine; CERT-UA